INDAHNYA PERBEDAAN HUKUM DALAM TRADISI MEMUKUL â€œKENTONGANâ€ (Telaah Kritis Kitab SharÄ¥ Hazz al-RaÃºs FÄ« Radd al-JÄsÃºs Karya Kiai Muhammad Faqih Maskumambang) - Wasid, Wasid (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
The scientific traditions of Islamic boarding schools in the archipelago or Nusantara have very unique characters because they are based on a very strong yellow book reference. In addition, Islamic boarding schools have become accustomed to interacting with differences of opinion, especially in responsing to laws regarding certain local traditions that develop in traditional Muslim environments. Various works have been produced in response to local traditional law with different issues. One of them is the work of KH. Muhammad Faqih Maskumambang Gresik entitled SharÄ¥ Hazz al-RaÃºs FÄ« Radd al-JÄsÃºs, a book that reveals the debate about the author with KH. Hasyim Asy'ari Jombang has to do with the traditional law of hitting Kentongan. The debate between the two senior figures of the pesantren and NU has given rise to noble traditions, namely even though they differ in the frame of mutual respect. His article only reveals the question of how epistemic reasoning used by Kiai Faqih Maskumambang and Kiai Hasyim Asy'ari in understanding the text of the Qur'an and hadith, as well as how the comments of the flu are related to the tradition of hitting the Kentongan ahead or after the adhan as a sign of entering prayer. Even though the arguments used are the same, only the conclusions of understanding give birth to very basic differences; a difference that describes local fiqh that is unique, and serious at the same time. The rest of the two remained together in difference. Together in NU and the Aswaja Islamic tradition, it is different because both have conclusions that are not the same in establishing the law of hitting kentongan.